A phase 1/2 study of carfilzomib in Japanese patients with relapsed and/or refractory multiple myeloma. (5th January 2016) - Watanabe, Takashi; Tobinai, Kensei; Matsumoto, Morio; Suzuki, Kenshi; Sunami, Kazutaka; Ishida, Tadao; Ando, Kiyoshi; Chou, Takaaki; Ozaki, Shuji; Taniwaki, Masafumi; Uike, Naokuni; Shibayama, Hirohiko; et al.
Summary: We conducted a phase 1/2 study of single‐agent carfilzomib in Japanese patients with relapsed/refractory multiple myeloma. Safety, pharmacokinetics and pharmacodynamics of carfilzomib were examined in phase 1. The primary endpoint in phase 2 was the overall response rate (ORR). Carfilzomib was administered in a twice‐weekly, consecutive‐day dosing schedule. In Phase 1, doses of 15 or 20 mg/m 2 were administered on this schedule or 20 mg/m 2 on Days 1 and 2 of Cycle 1 and then 27 mg/m 2 in the 20/27 mg/m 2 cohort. Patients had a median of five prior therapies, including bortezomib and an immunomodulatory agent. The dose level did not reach the maximum tolerated dose. The most common adverse events were haematological. Notably, carfilzomib either induced new hypertension ( n  = 4) or aggravated previously existing hypertension ( n  =   6) in 10 of 50 patients. Four of the eight patients who previously experienced peripheral neuropathy (PN) experienced a recurrence with carfilzomib use, but no new cases of PN occurred. The ORR of the 20/27 mg/m 2 40 patient cohort was similar to that in the pivotal US study. The dose was efficacious and tolerable in heavily pre‐treated Japanese patients; however, meticulous control of hypertension may be necessary for further carfilzomib use.